2011
DOI: 10.1089/ars.2010.3630
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Regulates Extracellular Superoxide Dismutase Activity and Expression in Neonatal Pulmonary Hypertension

Abstract: We previously demonstrated that superoxide and H 2 O 2 promote pulmonary arterial vasoconstriction in a lamb model of persistent pulmonary hypertension of the newborn (PPHN). Because extracellular superoxide dismutase (ecSOD) augments vasodilation, we hypothesized that H 2 O 2 -mediated ecSOD inactivation contributes to pulmonary arterial vasoconstriction in PPHN lambs. ecSOD activity was decreased in pulmonary arterial smooth muscle cells (PASMCs) isolated from PPHN lambs relative to controls. Exposure to 95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 50 publications
9
67
0
Order By: Relevance
“…Interestingly, we previously demonstrated that PPHN is associated with diminished ecSOD activity. 37 We hypothesize that increased expression of ecSOD in steroid-treated FPASMC might reduce oxidant stress in response to hyperoxia, in agreement with studies in rodents that have shown that overexpression of ecSOD attenuates hyperoxic lung injury. 43 One potential consequence of increased oxidative stress is activation of NFκB, a key transcription factor implicated in the pathogenesis of conditions associated with increased ROS, 19,44 including several pulmonary diseases such as primary pulmonary hypertension 45 and the development of chronic lung disease of prematurity.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, we previously demonstrated that PPHN is associated with diminished ecSOD activity. 37 We hypothesize that increased expression of ecSOD in steroid-treated FPASMC might reduce oxidant stress in response to hyperoxia, in agreement with studies in rodents that have shown that overexpression of ecSOD attenuates hyperoxic lung injury. 43 One potential consequence of increased oxidative stress is activation of NFκB, a key transcription factor implicated in the pathogenesis of conditions associated with increased ROS, 19,44 including several pulmonary diseases such as primary pulmonary hypertension 45 and the development of chronic lung disease of prematurity.…”
Section: Discussionsupporting
confidence: 87%
“…16,24,37 Given these differences, we used FPASMC isolated from PPHN lambs as a tool to investigate the aberrant vascular signaling pathways characteristic of PPHN and to determine the effect of hyperoxia on these pathways. Consequently, we investigated the effects of hydrocortisone in PPHN FPASMC to gain mechanistic insights into its beneficial effects on vascular function in intact PPHN lambs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These newborn lambs display increased PA pressure, pulmonary vascular remodeling, and other physiological changes consistent with clinical PPHN (31,49). Recent evidence suggests that PPHN lambs also exhibit elevated pulmonary vascular oxidant stress and a diminished antioxidant activity relative to control lambs (7,47), which may promote vasoconstriction directly and by impairing the activity of endothelial nitric oxide synthase (eNOS) and downstream cyclic guanozine monophosphate (cGMP) signaling (5,14,37).…”
Section: Introductionmentioning
confidence: 99%
“…Other agents which have shown promising results in laboratory studies by decreasing PVR and promoting vasodilation by various mechanisms include BAY 41-2272 (a novel GC activator), Fasudil (a Rho-kinase inhibitor), intrapulmonary recombinant human VEGF infusion (by upregulating eNOS), and intrapulmonary catalase administration (by decreasing ROS mediated vascular remodelling), high-dose hydrocortisone (by decreasing PDE5 and ROS activity, and increasing cGMP levels, sGC and SOD activity), apocynin (NADPH oxidase inhibitor improve oxygenation by attenuating ROS-mediated vasoconstriction and by increasing NOS activity, increased tetrahydrobiopterin (an eNOS co-factor) levels via sepiapterin supplementation (improves NO production by improving eNOS function and restoring angiogenesis), and antenatal betamethasone (improves response to pulmonary vasodilators by reversing increased superoxide/ decreased cGMP levels and restoring Hsp90-eNOS interactions) [71][72][73][74][75][76][77][78]. Thus, an antioxidant therapeutic approach may have multiple beneficial effects such as increased availability of endogenous and exogenous NO, reduced oxidative stress and reduced lung injury.…”
Section: Role Of Oxidant Stressmentioning
confidence: 99%